1996
DOI: 10.1128/jcm.34.6.1396-1400.1996
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Chlamydia trachomatis infections in asymptomatic men and women by PCR assay

Abstract: A PCR assay was evaluated for its ability to detect genital chlamydial infection in asymptomatic men and women. Urethral swab specimens were collected from 472 men for culture and PCR assay, and first-void urine (FVU) specimens were collected from 379 of these men for enzyme immunoassay (EIA) and PCR assay. Cervical swab specimens were collected from 242 women for culture, EIA, and PCR assay. Patients were considered infected if they were culture positive or positive by PCR with both plasmid-and major outer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…More recently, the use of nucleic acid amplification tests has enabled the detection of low copy numbers (Ͻ10 pg) of specific nucleic acids in a wide variety of genital specimens, including urine, and with claims of a sensitivity greater than that of immunoassays for detecting chlamydia lipopolysaccharide or outer membrane proteins (14,22). However, the use of clinical samples may be associated with inhibition in nucleic acid amplification tests (1,10,11,14,19,23) and may lead to variable sensitivity. This study compared the use of two commercially available nucleic acid amplification tests-Amplicor PCR (Roche Diagnostics) and ligase chain reaction (LCR; Abbott Laboratories) in urine samples-with culture and EIA in cer-vical or male urethral specimens for the detection of C. trachomatis.…”
mentioning
confidence: 99%
“…More recently, the use of nucleic acid amplification tests has enabled the detection of low copy numbers (Ͻ10 pg) of specific nucleic acids in a wide variety of genital specimens, including urine, and with claims of a sensitivity greater than that of immunoassays for detecting chlamydia lipopolysaccharide or outer membrane proteins (14,22). However, the use of clinical samples may be associated with inhibition in nucleic acid amplification tests (1,10,11,14,19,23) and may lead to variable sensitivity. This study compared the use of two commercially available nucleic acid amplification tests-Amplicor PCR (Roche Diagnostics) and ligase chain reaction (LCR; Abbott Laboratories) in urine samples-with culture and EIA in cer-vical or male urethral specimens for the detection of C. trachomatis.…”
mentioning
confidence: 99%
“…Consecutive men with no urethral symptoms presenting to the Ottawa-Carleton Sexual Health Centre, Ottawa, Ontario were asked to participate in the study as previously described (12). Of the 472 men who gave informed consent, information from the standardized questionnaire in-…”
Section: Study Subjectsmentioning
confidence: 99%
“…The advent of nucleic acid amplification technology, such as polymerase chain reaction (PCR), ligase chain reaction (LCR) and transcription mediated amplification, has brought dramatic improvements in test performance over culture and other nonculture tests because of lower detection thresholds. Recent studies have shown that the assays can also be used on FCU from both men and women (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, these nucleic acid-based assays are technically more demanding and more costly than nonculture tests such as EIA, which are currently used in most laboratories.…”
mentioning
confidence: 99%
See 2 more Smart Citations